The Strategic Orientation Dimensions İmpact On The Performance Of Micro Enterprises İn Kota Surabaya: Does The Mediating Role Of İnnovation Capability Matter? - Henrycus Winarto Santoso; Tri Ratnawati; Mohammad Sihab (Cita Konsultindo Research Center, 2024)
Firm performance is linked to strategic orientation and innovation capability. Only a few studies have examined the link between microenterprise performance, innovation capabilities, and strategy orientation—market, entrepreneurial, learning, technology, and network. Following this call, this study will evaluate the direct influence of strategic orientation dimensions on microenterprises in Kota Surabaya and construct a model to explain the mediation function of innovation capability. We conducted a cross-sectional study of 169 formal microenterprises under Kota Surabaya Cooperatives and Micro Enterprises Service supervision. A positivist perspective and quantitative methodology guided our SEM-PLS 2024 investigation. The results demonstrated that, first, technology orientation, one of the five strategic orientation dimensions, does not affect microenterprise performance. Four other strategic orientation dimensions directly improve microenterprise performance. Second, technology and network orientation, two of the five strategic orientation dimensions, do not affect innovation capabilities. The other three strategic orientation aspects directly improve microenterprise innovation capability. Third, innovation capability directly influences company performance and partially mediates the effects of learning, market, and entrepreneurial orientations. It doesn't mitigate the effects of network orientation and technology orientation.